1980
DOI: 10.1097/00000658-198010000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Is Amputation Necessary for Sarcomas? A Seven-Year Experience with Limb Salvage

Abstract: The rationale for amputation for local tumor control of skeletal and soft tissue sarcomas was based on results obtained from surgical therapy alone. However, our previous results from a pilot trial of multimodality therapy of preoperative chemotherapy and radiation therapy followed by surgical resection indicated that limb salvage (without amputation) could be accomplished in most patients with little morbidity and low recurrence rate. This report summarizes our experience in a prospective trial from January 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
3

Year Published

1982
1982
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(57 citation statements)
references
References 10 publications
1
52
1
3
Order By: Relevance
“…The multidisciplinary approach has brought significant advances in the local control of bone sarcomas, which allows more conservative attitudes in planning surgery, without detriment to the long-term survival rates [13,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multidisciplinary approach has brought significant advances in the local control of bone sarcomas, which allows more conservative attitudes in planning surgery, without detriment to the long-term survival rates [13,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two patients entered this protocol, which included neoadjuvant chemotherapy with three cycles with intra-arterial cisplatinum and systemic doxorubicin, repeated every 3 weeks and followed by a wide surgical en bloc tumor-bearing resection, with an IORT boost (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) to the tumor bed area.…”
Section: Osteosarcoma Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of local recurrence despite marginal resections in most of these patients, tumors larger than 10 cm in forty-five percent, and moderate or high-grade tumors in more than twothirds supports the efficacy of neoadjuvant combined chemoradiation or full dose radiation protocols. The combined chemoradiation approach (modified from Eilber et al [4]) has been used for all extremity sarcomas at our centre with 97% local control [5]. A Tri-Center Study confirmed local control rates of 98.5% [6].…”
Section: Discussionmentioning
confidence: 91%
“…Diese Art der Ausbreitung und die multizentrische Entstehung sind wichtige Ursachen ffir postoperative Lokalrezidive [7,10], ebenso die Streuung von Tumorzellen bei der Operation: selbst radikale Mal3nahmen, wie Amputationen, sind noch mit 10-15% Lokalrezidiven behaftet [1,12]. Um den Patienten nach M6glichkeit verstfimmelnde MaBnahmen zu ersparen, wurde in den beiden letzten Jahrzehnten die Kombination konservativer chirugischer Mai3nahmen mit der Strahlenbehandlung eingeffihrt [5,13,20,21]. Regionale Lymphknotenmetastasen sind selten (3-6%), auger bei Synovialsarkomen, Rhabdomyosarkomen, Leiomyosarkomen, Endotheloidsarkomen und malignen fibr6sen Histiocytomen (10 -30%) [ 12,27].…”
unclassified